2003
DOI: 10.2165/00019053-200321080-00001
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Economic Considerations in the Management of Prostate Cancer

Abstract: The purpose of this article was to provide an overview of the morbidity and mortality of prostate cancer, QOL issues and the economic impact of the disease. We searched Medline (from 1990 onwards) for all studies dealing with prostate cancer epidemiology, treatment, screening and staging, and critically reviewed the most relevant articles, focusing on pharmacoeconomic issues. Prostate cancer is the most common cancer in men. In the US, new estimated cases of prostate cancer represented 14.8% of all new cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Even though the reviewed studies demonstrated lower costs achieved with surgical castration, the authors concluded that orchiectomy could not be recommended when accounting for the extended indications for temporary hormone deprivation 53. In addition, the cost advantage of orchiectomy versus hormonal treatment may not be evident in all patients when considering the length of hospitalization following surgery and the duration of hormonal treatment being critical in economic evaluation 54. In Sweden, orchiectomy and hormonal treatments were found to be equivalent at 8 days of hospitalization and 18 months of hormonal treatment 55.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the reviewed studies demonstrated lower costs achieved with surgical castration, the authors concluded that orchiectomy could not be recommended when accounting for the extended indications for temporary hormone deprivation 53. In addition, the cost advantage of orchiectomy versus hormonal treatment may not be evident in all patients when considering the length of hospitalization following surgery and the duration of hormonal treatment being critical in economic evaluation 54. In Sweden, orchiectomy and hormonal treatments were found to be equivalent at 8 days of hospitalization and 18 months of hormonal treatment 55.…”
Section: Discussionmentioning
confidence: 99%
“…These effects also limit the radiation dose applied, which is the most important factor affecting the efficacy of this treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to 20 percent of patients with acute radiation proctitis will have symptoms that are severe enough to necessitate an interruption in radiation treatment [16,28,29]. In patients with persistent or severe bleeding due to chronic radiation Colo-Proctopathy (CRCP) and that fail to respond to sucralfate therapy for four weeks, endoscopic therapy with (APC, formalin, and BEC) are indicated [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Other effective therapies described are the argon and Nd: YAG laser, cryoablation, bipolar electrocoagulation (BiCap), heater probe, hyperbaric oxygen therapy (HBO), hormonal therapy, antioxidants and metronidazole [26,27]. Several studies including systematic reviews have reported an improvement in symptoms, but it is still not sufficiently clear which therapy is better [28,29].…”
Section: Journal Of Adenocarcinoma Issn 2572-309xmentioning
confidence: 99%